(untitled) (Agricultural Engineering, 2023)
The milling process has evolved over time, employing various techniques to produce flour with different particle sizes and applications. This paper discusses the advancements in the wheat flour milling process and examines their impact on flour quality. The concept of wheat milling value is also introduced, which refers to the ability of wheat to produce flour with desirable properties and high yield. The importance of wheat cleaning in the milling process is highlighted, along with technological advancements such as color sorting machines and debranning of wheat grains before grinding, which facilitate efficient cleaning and increase flour yield. The progress of wheat conditioning in preparing wheat for milling is also discussed, along with current trends in grinding the wheat kernel. These advancements collectively contribute to enhancing flour quality, production efficiency, and overall milling performance.